Using ERA-5 LAND reanalysis rainfall data to better evaluate the performance of the regional shallow landslide early warning system of Piemonte (north-western Italy) in the context of climate change - Botto, Valentina; Tiranti, Davide; Barbarino, Simona; Ronchi, Christian (Frontiers in Earth Science, 2025)
To correctly understand how and whether climate change has influenced the behavior of shallow landslide events over the last century, it is essential to carefully identify the historical series of phenomena and their respective triggering causes, as well as to accurately select the most appropriate analytical tools to minimize the degree of uncertainty in statistical correlation of causes and effects. Shallow landslide events occurring from 1960 to 2023 in Piemonte (NW Italy) are considered here, for which the primary triggering cause is represented by rainfall events, with a negligible contribution from antecedent precipitations. This paper is an update of a previous study, adding to the analysis recent widespread landslide events covering a wider time range with new precipitation data (additional 4 years). The primary difference lies in the use of a different method to analyze the rainfall responsible for the occurrence of shallow landslides. In particular, the results obtained for 24 and 48 h rainfall durations, when compared with the triggering thresholds of the R-SLEWS (previously employed the Optimal Interpolation Method), are verified using new and more flexible method for reconstructing triggering rainfall based on ERA5-Land hourly precipitation data. The new approach moderately improves the identification of actual triggering rainfall over 24 h but is less performant when it comes to identifying triggering shallow landslides over 48 h. Where no significant improvements in the detection of rainfall-inducing shallow landslide events are obtained, the method can still be effectively used in areas with a sparser rain gauge network, which can rely less on observed precipitation data.